Coordination of bis(pyrazol-1-yl)amine to palladium(II): influence of the co-ligands and counter-ions on the molecular and crystal structures. (January 2015) - Mendoza, M. de los A.; Bernès, S.; Mendoza-Díaz, G.
No abstract available